Exponent matrices and Frobenius rings - Dokuchaev, M.A.; Kasyanuk, M.V.; Khibina, M.A.; Kirichenko, V.V. (Algebra and Discrete Mathematics, 2014)
We give a survey of results connecting the exponent matrices with Frobenius rings. In particular, we prove that for any parmutation σ ∈ Sn there exists a countable set of indecomposable Frobenius semidistributive rings Am with Nakayama permutation σ.